Productive evaluation of dairy cows fed with urea protected by protein nanoparticle in partial replacement of soybean meal - Ribeiro, Deivid Roni; Sviech Ratim, José Leonardo; Ribeiro, Kauane Maria; de Almeida, Rodrigo; Ostrensky, André; Anater, Amanda; Turra Pimpão, Cláudia (Revista Acadêmica Ciência Animal, 2021)
The objective of this study was to evaluate productive and metabolic responses of dairy cows fed a diet with urea protected by protein nanoparticles. The experimental design was a crossover with three groups of 15 cows each and three periods of 21 days. In each period the animals were fed one of the isonitrogenated and isocaloric diets: SM = without substitution of soybean meal; CU = substitution of soybean meal by 0.52% conventional urea; PU = soybean meal substituted by 0.59% urea protected by nanoparticles. The yield and composition of milk, the blood and urine biochemical parameters, as well the allantoin:creatinine ratio as a predictor of microbial protein absorption were measured. No significant differences were found (p >0.05) in milk yield and composition, in urinary biochemistry and in allantoin:creatinine ratio. The average values of plasma ureic nitrogen (PUN) in mg.dL-1 after the morning feeding did not differ significantly (p >0.05) in the CU (20.65) and PU (20.25), but both were higher (p <0.05) when compared to SM (19.52). Inclusions of 0.59% urea protected by nanoparticles do not affect the productive performance of dairy cows. The similar values of PUN between the treatments CU and PU suggest that the behavior of the release and the absorption of ammonia in the rumen is similar between these two types of urea which were evaluated, but the use of ground corn is important to reach these results.